2020
DOI: 10.1038/s41598-020-64462-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and accuracy of a robotic guidance system for navigated spine surgery in a hybrid operating room: a cadaver study

Abstract: Adrian elmi-terander 1,2 the combination of navigation and robotics in spine surgery has the potential to accurately identify and maintain bone entry position and planned trajectory. The goal of this study was to examine the feasibility, accuracy and efficacy of a new robot-guided system for semi-automated, minimally invasive, pedicle screw placement. A custom robotic arm was integrated into a hybrid operating room (OR) equipped with an augmented reality surgical navigation system (ARSN). The robot was mounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Although there is a low morbidity of complications, a misplaced screw can result in neurovascular damage, dural tearing, or visceral involvement. Therefore, robot-assisted techniques are designed to help spinal surgeons with more precision and convenience of pedicle screw placement [14][15][16]. Gao et al performed a metaanalysis including six studies involving 158 patients (688 pedicle screws) in a robot-assisted group and 148 patients (672 pedicle screws) in a freehand group, and showed that the robot-assisted technique was associated with equivalent accuracy rate of pedicle screw implantation, fewer proximal facet joint violations, and less intraoperative radiation exposure, but longer surgical duration than that with the freehand technique [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a low morbidity of complications, a misplaced screw can result in neurovascular damage, dural tearing, or visceral involvement. Therefore, robot-assisted techniques are designed to help spinal surgeons with more precision and convenience of pedicle screw placement [14][15][16]. Gao et al performed a metaanalysis including six studies involving 158 patients (688 pedicle screws) in a robot-assisted group and 148 patients (672 pedicle screws) in a freehand group, and showed that the robot-assisted technique was associated with equivalent accuracy rate of pedicle screw implantation, fewer proximal facet joint violations, and less intraoperative radiation exposure, but longer surgical duration than that with the freehand technique [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, robotics in spinal surgery were predominantly designed as navigational devices for pedicle screw insertion, such as the Mazor X (Medtronic and Mazor Robotics, Medtronic, Minneapolis, MN, USA), ROSA (Med Tech Surgical, Inc., Newark, NJ, USA), and Excelsius GPS (Globus Medical, Inc., Audubon, PA, USA) [9][10][11]. Multiple studies have reported early experiences with robot-assisted pedicle screw placement and the outcomes are promising [12][13][14]. Increasingly, researchers have already focused on the combination of MIS and robotic navigation to improve the e ciency and accuracy of spinal surgeries [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a low morbidity of complications, a misplaced screw can result in neurovascular damage, dural tearing, or visceral involvement [18]. Therefore, robot-assisted techniques are designed to help spinal surgeons with more precision and convenience of pedicle screw placement [14][15][16]. Gao et al performed a metaanalysis including six studies involving 158 patients (688 pedicle screws) in a robot-assisted group and 148 patients (672 pedicle screws) in a freehand group, and showed that the robot-assisted technique was associated with equivalent accuracy rate of pedicle screw implantation, fewer proximal facet joint violations, and less intraoperative radiation exposure, but longer surgical duration than that with the freehand technique [12].…”
Section: Discussionmentioning
confidence: 99%
“…In order to study the puncture accuracy of robot-assisted ARSN system. In 2020, Gustav et al proposed that the robot be integrated into a hybrid operating room equipped with ARSN system for semi-automatic and minimally invasive pedicle screw placement [52]. The feasibility, accuracy and effectiveness of the guidance system are verified.…”
Section: Discussionmentioning
confidence: 99%